Convergence of Values between Islamic Finance and Socially Responsible Investment (SRI): What are the Limits of SRI Sukūk Issuance? - Radzi, Rafisah Mat; Sakai, Minako (Journal of King Abdulaziz University: Islamic Economics, 2022)
Ethical investments, such as socially responsible investment (SRI), and faith-based investments, such as Islamic finance, have become commonplace in the economic development discourse. Given that SRI bonds dominate SRI markets, one might ask why SRI Sukūk (Islamic bonds) have not contributed more to certain social or sustainability-related causes or sectors to achieve the objectives of Sharīʿah (Islamic law). This study will mainly examine the aspects considered ethically or socially responsible as incorporated in SRI and Islamic finance. In doing so, this study will compare the values or principles of SRI bonds and the SRI Sukūk framework to enable Islamic finance players to make good use of the opportunity of the segment. This study further examines what limits the involvement of Islamic financial market participants in socially responsible investment. Drawing on the 2014 SRI Sukūk framework and other SRI legislation, this study reveals that both have similar qualities, characteristics and objectives. However, SRI sukuk are challenged by investors’ appetite for a profitable return, lack of awareness of social investment and lack of data and methodology associated with the Triple Bottom Line or 3Ps (people, planet and profit) approach. These problems have, to some extent, limited the Islamic financial market players from investing in social responsibility programes.